Jurassic-Pliocene biogeography: testing a model with velvet worm (Onychophora) vicariance - Monge-Nájera, Jorge (Revista de Biología Tropical, 1996)
Summary paleomaps of global continental vegetation from the Jurassic through the Pliocene were prepared (based on the literature) and used to define an area cladogram. Bouvier’s natural classification of velvet worms (phylum Onychophora) was used to define a taxonomiclgeographic cladogram of onychophorans for all regions where they are found today. Both cladograms show the same sequence oC geographic vicariance. Thus, the paleogeographic model is supported by the taxonomic evidence. The paper includes a color atlas